An approach to handling inconsistent ontology definitions based on the translation of description logics into defeasible logic programming - Gómez, Sergio Alejandro (2006)
The Semantic Web is a future vision of the web where stored information has exact meaning, thus enabling computers to understand and reason on the basis of such information. Assigning semantics to web resources is addressed by means of ontology definitions which are meant to be written in an ontology description language such as OWL-DL that is based on so-called Description Logics (DL). Although ontology definitions expressed in DL can be processed with existing DL reasoners, such DL reasoners are incapable of dealing with inconsistent ontology definitions. Previous research has determined that a subset of DL can be effectively translated into an equivalent subset of logic programming. We propose a method for dealing with inconsistent ontology definitions in the Semantic Web. Our proposal involves mapping DL ontologies into equivalent DeLP programs. That is, given an OWL-DL ontology OOwl, an equivalent DL ontology ODL can be obtained. Provided ODL satisfies certain restrictions, it can be translated into an equivalent DeLP program ODeLP . Therefore, given a query Q w.r.t. OOwl, a dialectical process will be performed to determine if Q is warranted w.r.t. ODeLP .